Course Outcomes, Program Outcomes, Co-Po Mapping and Bloom’s Taxonomy Geomorphology Of Course Code: Geo-C-501 Postgraduate Sikkim University - Tanka Prasad Dhungel, Chandra Prasad Khatiwada (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
This abstract provides a concise overview of the integration of Course Outcomes (COs), Program Outcomes (POs), and Bloom's Taxonomy in educational assessment and curriculum design of Geomorphology Of Course Code: Geo-C-501 Postgraduate Sikkim University. Course Outcomes define specific learning achievements expected from students at the end of a course. Program Outcomes are broader goals that graduates are expected to attain through the entire academic program. Bloom's Taxonomy serves as a hierarchical classification of cognitive skills, from basic knowledge recall to complex analysis and creation. The alignment of COs and POs using Bloom’s Taxonomy enables institutions to systematically evaluate and enhance student learning, ensuring academic programs meet educational standards and industry expectations. This structured mapping improves teaching strategies, helps in achieving accreditation requirements, and promotes continuous improvement in higher education.